Enhancing photocatalytic partial oxidation of methane to methanol: Experimental investigation of 2D/metal oxide composite catalysts - Amira Chebbi (19756983) (2025)
This study investigates the potential of photocatalytic processes for the selective conversion of methane into valuable liquid fuels, particularly methanol, addressing the need for efficient, alternative, and clean energy carriers and fuels. Two pristine photocatalysts, W₁₈O₄₉ and g-C₃N₄, along with their respective composite W₁₈O₄₉/g-C₃N₄, were synthesized and analyzed using SEM, TEM, XRD, XPS, BET, and UV-VIS spectroscopy techniques. Additionally, transient photocurrent measurements and electrochemical impedance spectroscopy (EIS) were conducted to elucidate charge transfer mechanisms and interfacial properties of the photocatalysts. The photocatalytic performance was evaluated under both visible and UV light conditions. Among the three catalysts tested, the composite W₁₈O₄₉/g-C₃N₄ demonstrated remarkable catalytic activity of 62.3 μmol g−1 h−1 under visible light, nearly 4-fold higher than pristine W₁₈O₄₉ and 5-fold higher than g-C₃N₄. The enhanced performance is attributed to the forming of a Z-scheme heterojunction system, as evidenced by XPS analysis showing increased oxygen vacancy density and strong electronic coupling between the components, further confirmed by electrochemical characterization revealing improved charge separation efficiency. This composite system offers a sustainable and cost-effective alternative to noble metal-based catalysts for photocatalytic methane conversion, demonstrating significant potential for clean energy production and greenhouse gas mitigation. Other Information Published in: Journal of Photochemistry and Photobiology A: Chemistry License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jphotochem.2025.116765